2001
DOI: 10.1097/00004872-200109000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Progression of functional and structural cardiac alterations in young normotensive uncomplicated patients with type 1 diabetes mellitus

Abstract: Uncomplicated type I diabetes mellitus is characterized by early structural and functional cardiac alterations. Some of these alterations show a measurable progression within a relatively short time span.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 40 publications
2
23
1
1
Order By: Relevance
“…Both serum cholesterol and glycemic control predicted higher systolic BP in our study. Abdelghaffar et al and Carugo et al have reported a similar difference in blood pressures of diabetics versus controls in their studies [32, 33]. However, Aepfelbacher et al did not document any difference in BP of T1DM even after a documented improvement in HbA1C [34].…”
Section: Discussionmentioning
confidence: 94%
“…Both serum cholesterol and glycemic control predicted higher systolic BP in our study. Abdelghaffar et al and Carugo et al have reported a similar difference in blood pressures of diabetics versus controls in their studies [32, 33]. However, Aepfelbacher et al did not document any difference in BP of T1DM even after a documented improvement in HbA1C [34].…”
Section: Discussionmentioning
confidence: 94%
“…19,20 Indeed, echocardiography performed in 87 patients with type 1 diabetes mellitus without known coronary artery disease revealed diastolic dysfunction with a reduction in early diastolic filling, an increase in atrial filling, an extension of isovolumetric relaxation, and increased numbers of supraventricular premature beats. 21 In similar subjects with uncomplicated type 1 diabetes without clinically apparent macrovascular or microvascular complications, Carugo et al 22 reported early structural and functional cardiac alterations such as increased LV wall thickness and LV mass index, an age-related decline in ejection fraction, and an age-related increase in diastolic diameter. Similar approaches in well-controlled subjects with type 2 diabetes have revealed a prevalence of diastolic dysfunction of up to 30%.…”
Section: Human Studiesmentioning
confidence: 99%
“…Likewise, a long-term prospective study of T1DM found no significant changes to myocardium structure suggesting that diabetes may not have direct effects on the heart ( Genuth, et al, 2013;Litwin, 2013). However, various human and animal studies have shown the development of diastolic dysfunction alongside structural changes to the myocardium ( Carugo, et al, 2001;Joffe, et al, 1999;Pacher, et al, 2002;Schannwell, Schneppenheim, Perings, Plehn, & Strauer, 2002;Shivalkar, et al, 2006). In contrast, T2DM strongly is associated with HF (de Simone, et al, 2010).…”
Section: Is Diabetic Cardiomyopathy a Distinct Phenotype?mentioning
confidence: 99%